The Effect of Massage Therapy and Stretching Therapy on Chronic Low Back Pain in Athletes - Baharsyah, Arizal Septian; Sulaiman; setiawan, ipang (Universitas Negeri Semarang, 2024)
Chronic low back pain (CLBP) is a prevalent issue among athletes, significantly impacting their performance and quality of life. This study investigates the comparative effectiveness of different combinations of massage therapy and stretching therapy in reducing CLBP. Using a 2x2 factorial experimental design, 24 athletes were randomly divided into four groups: thumb massage with self-stretching, thumb massage with assisted stretching, knuckle massage with self-stretching, and knuckle massage with assisted stretching. Each group consisted of six athletes receiving one treatment session. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after treatment. Results indicated a reduction in pain intensity across all groups, with the highest average reduction observed in the knuckle massage with assisted stretching group, followed by knuckle massage with self-stretching, thumb massage with assisted stretching, and thumb massage with self-stretching groups. The study concludes that the combination of massage and stretching therapies effectively reduces CLBP in athletes, with knuckle massage combined with assisted stretching showing the most significant reduction. No significant interaction between massage and stretching therapies was found suggesting the independent efficacy of each therapy. These findings support the use of these non-invasive treatments in managing CLBP among athletes.